Hubungan Media Pembelajaran Digital Dengan Literasi Digital Peserta Didik Pada Mata Pelajaran Agama Buddha - Ristiani, Trina; Praptiyono, Kabul; Budiyanto, Budiyanto (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
The study aims to examine the correlation between the use of digital learning media and the digital literacy skills of Buddhist students in learning activities in the 2024/2025 academic year. The main focus of the study is to determine the form of relationship, direction, and level of closeness between the two variables. The phenomenon observed in Buddhist students at SMA Negeri 1 Ampel shows that although the use of digital media in learning is quite active, students' abilities in understanding, evaluating, and managing digital information are not optimal. The approach used in this study is the correlational quantitative method. Meanwhile, the data was obtained by distributing questionnaires to all samples totaling 18 respondents. The results of the hypothesis test showed that there was a positive and significant relationship with a contribution of 73% between the use of digital learning media and digital literacy. This shows that the increasing use of digital learning media will also increase students' digital literacy. Meanwhile, the remaining 27% is influenced by other factors outside the variables studied. This study provides implications that the integration of appropriate digital media can strengthen digital literacy in the context of learning based on Buddhist values.